Control co-design of 13 MW downwind two-bladed rotors to achieve 25% reduction in levelized cost of wind energy. (2021) - Pao, Lucy Y.; Zalkind, Daniel S.; Griffith, D. Todd; Chetan, Mayank; Selig, Michael S.; Ananda, Gavin K.; Bay, Christopher J.; Stehly, Tyler; Loth, Eric
Abstract: Wind energy is recognized worldwide as cost-effective and environmentally friendly and is among the fastest-growing sources of electrical energy. To further decrease the cost of wind energy, wind turbines are being designed at ever larger scales, which is challenging due to greater structural loads and deflections. Large-scale systems such as modern wind turbines increasingly require a control co-design approach, whereby the system design and control design are performed in a more integrated fashion. We overview a two-bladed downwind morphing rotor concept that is expected to lower the cost of energy at wind turbine sizes beyond 13 megawatts (MW) compared with continued upscaling of traditional three-bladed upwind rotor designs. We describe an aero-structural-control co-design process that we have used in designing such extreme-scale wind turbines, and we discuss how we were able to achieve a 25% reduction in levelized cost of energy for our final turbine design compared to a conventional upwind three-bladed rotor design. Graphical abstract: Highlights: Downwind rotor designs allow for load-alignment and significantly lighter blades. Aero-structural-control co-design iterations yield lower cost-of-wind-energy designs. Longer more slender blades increase power capture with small increase in turbine cost.